THE EFFECTS OF WARM COMPRESS TO VOIDING REFLEXES ON POST OPERATIVE SPINAL ANESTHESIA - Djunizar Djamaludin; Amila Amila; Suci Asianti (Malahayati International Journal of Nursing and Health Science, 2019)
Background: Spinal anesthesia commonly can lead to urinary retention because the patient cannot feel his bladder is full and unable to initiate for voiding after the surgery. This is caused by bladder and sphincter muscles are unable to respond for voiding reflexes. One of nursing intervention to prevent of urinary retention is warm compress on supra pubic area for postoperative patient undergo spinal anesthesia.Purpose : This study was to examinethe effect of warm compress to recovery of voiding reflexes ont postoperativepatient undergo spinal anesthesia at Pertamina Bintang Amin Hospital, Bandar LampungMethods : A quasiexperimental study was conducted usingintervention and control groups with simple random sampling technique was applied. There were 30 postoperative patientsundergo spinal anesthesia were recruited at Pertamina Bintang Amin Hospital Bandar Lampung.Result : The mean score of intervention group with warm compression was 6.67 hours (ranging from 6to 8). The mean score of control group withoutwarm compress was7.13 hours (ranging from 5t o 9).Conclusion: Nursing intervention by applying warm compress is necessary to recovery of voiding reflex on postoperative patient with spinal anesthesia.